2012
DOI: 10.1136/jmedgenet-2012-101191
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in XRCC2 as breast cancer susceptibility alleles: Table 1

Abstract: Our data do not confirm an association between XRCC2 variants and breast cancer risk, although a relative risk smaller than two could not be excluded. Variants in XRCC2 are unlikely to explain a substantial proportion of familial breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 9 publications
1
48
1
2
Order By: Relevance
“…18 The extent of the impact of this gene on breast cancer risk was questioned by a subsequent study. 19 The PALB2 (partner and localizer of BRCA2) gene, which encodes a direct interactor of BRCA2-namely, RAD51-and other proteins, 20 has been actively studied as a breast cancer risk factor, and sequencing of its coding regions revealed that deleterious mutations are present in several populations. The first study that indicated that PALB2 is a breast cancer gene reported germ-line truncating mutations in 10/923 (1.1%) English familial breast cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…18 The extent of the impact of this gene on breast cancer risk was questioned by a subsequent study. 19 The PALB2 (partner and localizer of BRCA2) gene, which encodes a direct interactor of BRCA2-namely, RAD51-and other proteins, 20 has been actively studied as a breast cancer risk factor, and sequencing of its coding regions revealed that deleterious mutations are present in several populations. The first study that indicated that PALB2 is a breast cancer gene reported germ-line truncating mutations in 10/923 (1.1%) English familial breast cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson et al [25] analyzed 33 BC patients from 15 families, but their findings were limited to the genes, whose breast cancer predisposing role had already been demonstrated in prior studies [9,27,137]. Park et al [28] suggested a role of very rare mutations in XRCC2 gene; however, subsequent reports failed to replicate these findings [138,139]. Hilbers et al [134] and GraciaAznarez et al [22] analyzed several well-selected families, but no major new gene was identified.…”
Section: Breast Cancermentioning
confidence: 95%
“…Damit ist eine Aufnahme dieses Gens in die Routinediagnostik definitiv nicht gegeben. Außerdem konnte der ursprüngliche Befund auch international in einem größeren Kollektiv nicht bestätigt werden [18].…”
Section: Identifizierung Weiterer Risikogene Durch Next Generation Seunclassified